Rekonstruksi Teori Self-Regulated Learning dalam Perspektif Psikologi Pendidikan Islam: Kajian Literatur di Era VUCA - Nor Amalia Abdiah; Fatikhatun Nur; Miftahatur Rizqiyah; Hamimah Hamimah; Jimmy Malintang; Hennira Rohyatin (Institut Nalanda, 2026)
The VUCA era presents new challenges to students’ self-regulation skills, particularly in coping with the complexities of digital learning, psychological pressures, and rapid social change. Research on self-regulated learning has thus far been dominated by modern educational psychology approaches that focus on cognitive and performance-based aspects, leaving spiritual and moral dimensions without adequate attention. This study aims to reconstruct the concept of self-regulated learning from the perspective of Islamic educational psychology. The study employs a qualitative approach using library research. Data were collected through a review of various academic books, national journals, and reputable international journals relevant to self-regulated learning, Islamic educational psychology, and education in the VUCA era. Data analysis was conducted using content analysis and conceptual analysis. The results indicate that the reconstruction of self-regulated learning from the perspective of Islamic educational psychology involves the integration of cognitive, spiritual, moral, and reflective dimensions through the concepts of muhasabah, muraqabah, mujahadah, and tazkiyatun nafs. This approach contributes to building students’ psychological resilience, learning discipline, moral awareness, and spiritual responsibility in the VUCA era.